2017
DOI: 10.1097/mot.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Heart xenotransplantation

Abstract: The studies in this review highlight efforts in multiple disciplines to optimize perioperative and postxenotransplant outcomes. In examining these individual topics, this article reflects the exciting and ongoing progress in the field of cardiac xenotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This therapy will be expensive. All transplantation is associated with immunosuppression costs, but additional expensive novel immunotherapy may be required for xenotransplantation 29 . Competition among the companies involved in creating these organs might keep the costs in check, but this seems not to have happened with many medical therapies.…”
Section: Efficacy Access and Expense—short And Long Termmentioning
confidence: 99%
“…This therapy will be expensive. All transplantation is associated with immunosuppression costs, but additional expensive novel immunotherapy may be required for xenotransplantation 29 . Competition among the companies involved in creating these organs might keep the costs in check, but this seems not to have happened with many medical therapies.…”
Section: Efficacy Access and Expense—short And Long Termmentioning
confidence: 99%
“…Through a combination of many discoveries in enhanced immunosuppression and genetic engineering as well as a better understanding of cross-species incompatibilities, the field of xenotransplantation has made significant progress in the last decade. As a result, cardiac xenograft survival has been demonstrated for more than three years [57]. With the correct immunosuppressive regimen, xenograft survival can be extended.…”
Section: Future Of Xenotransplantationmentioning
confidence: 99%
“…For the long-term survival of other xenografts including heart, kidney, and islet cells, treatment with costimulation blockade agents is also crucial for maintenance therapy in most pig-to-NHP transplantation experiments ( Chan and Mohiuddin, 2017 ; Cooper et al, 2018 ; Higginbotham et al, 2015 ; Liu et al, 2017 ; Wijkstrom et al, 2017 ). Only two studies showed long-term survival of neonatal or embryonic islet xenotransplants with CD40/CD154 pathway-sparing regimens using rituximab, anti-thymocyte globulin (ATG), and belatacept as induction regimens; and abatacept, everolimus, and FTY720 as maintenance therapy ( Hecht et al, 2009 ; Thompson et al, 2012 ).…”
Section: Immunomodulating Agents In Xenotransplantationmentioning
confidence: 99%